Association of HLA class II and history of atopy and frequent relapse of childhood steroid-sensitive nephrotic syndrome - Dany Hilmanto (Indonesian Pediatric Society, 2007)
Background The association between HLA class II and frequentrelapse of nephrotic syndrome (FRNS) has been reported.Objective To identify the association between HLA class II,history of atopy, and upper respiratory tract infection (URTI)with FRNS.Methods This was a case control study conducted at theDepartment of Child Health, Hasan Sadikin Hospital Bandungand Cipto Mangunkusumo Hospital Jakarta from November 2002to October 2003 on children aged 1-14 years with FRNS. Thesubjects consisted of 40 FRNS and 84 healthy children. HLAclass II was typed by polymerase chain reaction-sequence specificoligonucleotide (PCR-SSO) in Leiden, the Netherlands. Theassociation between HLA class II and FRNS was expressed byodds ratio (OR). The association between such factors and FRNSwas analyzed by logistic regression.Results Atopy was higher in patients than that in controls(P=0.013). URTI did not differ in both groups (P=0.173). HLA-DRB1*03 and DRB1*04 (OR=4.43, P=0.03), DQB1*02(OR=3.43, P=0.00), and DQB1*04 (OR=12.06, P=0.01) weresignificantly higher among patients than those in controls whereasHLA-DRB1*12 (OR=0.34, P=0.02) and DQB1*0301p(OR=0.35, P=0.02) were significantly lower among patients thanthose in controls. Using logistic regression analysis, only HLA-DRB1*12, DQB1*02 and atopy took part in FRNS.Conclusion HLA-DRB1*12, DQB1*02, and atopy all togetherhave association with FRNS.